A new species of the genus Petrobia Murray (Prostigmata, Tetranychidae) and complementary description of Petrobia cardi Chaudhri - Muhammad Kamran; Fahad Alatawi (Biodiversity Data Journal)
A new species, Petrobia (Petrobia) pakistanensis sp. nov. is described and collected, based on females form wild grasses, from Pakistan. the species P. (Tetranychina) cardi Chaudhri, W.M., 1972 is re-described and illustrated, based on femles and male.Petrobia (Petrobia) pakistanensis sp. nov. (Prostigmata, Tetranychidae) is described and illustrated, based on female specimens collected from wild grasses (Poaceae) from Azad Kashmir, Pakistan. The male of P. (Tetranychina) cardi Chaudhri, reported for the first time, is described and illustrated. Additionally, the complementary description of females of this species is provided, based on a new collection.